اثر الذكاء الاجتماعي في تبني المسؤولية الاجتماعية دراسة لعينة من أطباء القطاع الخاص - مديني, عثمان; يغني, سامية (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الورقة البحثية التعرف على أسباب تراجع تنافسية للقطاع الصحي الخاص بالجزائر لصالح جهات أجنبية باتت تستقطب شرائح كبيرة من المجتمع الجزائري مفضلة ما تعرضه من خدمات علاجية ،حيث اهتمت الدراسة بتشخيص العوامل المادية، كالتجهيزات والمرافق وتوزيع الأطباء في دراسة مقارنة بين الجزائر وتونس ومن ثم التطرق الى مقاربات لها علاقة بالقدرة على إدارة العلاقات العامة من خلال دراسة اثر الذكاء الاجتماعي لعينة من الاطباء الخواص بالجزائر على تبني المسؤولية الاجتماعية. اعتمدنا في هذه الدراسة عبر تطوير لاستبيان ضم 54 سؤالا مقسم إلى خمس محاور تثمل أبعاد الذكاء الاجتماعي وتم استخدام الرزمة الإحصائية لتحليلها، وتوصلت الدراسة إلى عدم وجود اثر لمستويات الذكاء الاجتماعي على تبني المسؤولية الاجتماعي كفلسفة بإمكانها تعزيز صورة الجيدة للقطاع، وأوصت الدراسة بضرورة تفعيل فلسفة المسؤولية الاجتماعية للقطاع الصحي الخاص وترجمتها عمليا من خلال برامج تأطير جماعي يعزز الصورة الذهنية ويعمل على استعادة الثقة المفقودة This research paper aims to identify the reasons for the compétitive retreat of the health sector in Algeria for the benefit of foreign entities that are attracting large segments of the Algerian society, preferring what it offers from treatment services, as it focused on diagnosing physical factors, such as equipment, facilities and the number of doctors through a comparative study between Algeria and Tunisia and then studying approaches to it Relationship to the ability to manage public relations by studying the impact of social intelligence of a sample of private doctors in Algeria on adopting social responsibility in a sensitive sector. We adopted this study through the development of a questionnaire that included 54 questions divided into five axes that include the dimensions of social intelligence and the statistical package was used to analyze it, and the study found that there is no impact of levels of social intelligence on the adoption of social responsibility as a philosophy that can enhance the good image of the sector, and the study recommended the necessity of activating the philosophy of responsibility Social work for the private health sector and translated in practice through group framing programs that enhance the mental image
The impact of social intelligence in the adoption of social responsibility Study of a sample of private doctors
مقال
Keywords: الذكاء الاجتماعي ; المسؤولية الاجتماعية ; الصورة الذهنية